Mathematics and life sciences - Antoniouk, Alexandra V.; Melnik, Roderick V.N. (De Gruyter series in mathematics and life sciences, 2013)
The book provides a unique collection of in-depth mathematical, statistical, and modeling methods and techniques for life sciences, as well as their applications in a number of areas within life sciences. It also includes a range of new ideas that represent emerging frontiers in life sciences where the application of such quantitative methods and techniques is becoming increasingly important. The book is aimed at researchers in academia, practitioners and graduate students who want to foster interdisciplinary collaborations required to meet the challenges at the interface of modern life sciences and mathematics.
Includes bibliographical references and index
Keywords: Naturwissenschaften; Mathematik; Biomathematik